Meningkatkan Kinerja Guru Dengan Kompetensi Melalui Kepuasan Kerja dan Motivasi Intrinsik Sebagai Variabel Intervening (Studi Pada SMK Negeri di Kota Serang) - Siti Teti Azmah Barat; Wawan Prahiawan; Lutfi (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
This study aims to examine and analyze the effect of competence on teacher performance through job satisfaction and intrinsik motivation. This study uses a descriptive quantitative method with a causal approach. The object of this research is SMK Negeri in Serang City using a sample of 144 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Competence affects teacher performance. 2). Competence affects job satisfaction. 3). Competence has an effect on intrinsik motivation. 4). Job satisfaction has an effect on teacher performance. 5). Intrinsik motivation has an effect on teacher performance. Job satisfaction and intrinsik motivation can mediate between competencies in partial mediation.